The Spatiotemporal Cyclicality of the Circular Narrative of The Good Place (ENTHYMEMA, 2025)
The paper aims to pay attention to the cyclicity of space and time representation of the afterlife in The Good Place. Here the protagonists are stuck in an infernal loop and every time they discover they are in a particularly elaborate infernal circle, their memory is erased and the narration restart. When the story starts over, the demonic narrative is always slightly different from the previous one. The cyclical nature of the narration at a space-time level would seem to perfect the storytelling: through the alteration of the narrative structure, traditional expectations relating to the afterlife are demolished and a dystopian afterlife is narrated.
Keywords: Storytelling; Spacetime; Seriality; Ethics; The Good Place